KERENTANAN DAN UPAYA ADAPTASI MASYARAKAT PESISIR TERHADAP PERUBAHAN IKLIM - Niken Sakuntaladewi; Sylviani Sylviani (Jurnal Penelitian Sosial dan Ekonomi Kehutanan, 2014)
Climate change is being understood by the local communities as seasonal change and has caused many negative impacts to the livings. This article aims to analyse vulnerability of the coastal communities due to climate change. Research was conducted in three villages located around mangrove forests functioning as protected forest in Subang Regency, conservation forest in Jembrana Regency, and private forest in Pemalang Regency. Data was collected from thirty respondents per village, and analyzed with Multivariate Analysis. Research shows that climate change has lowered the incomes of majory of the rural communities. The number of community living in private forest is the least vulnerable (37%), follows consecutively by those in conservation forest (55%), and the most vulnerable ones is (82%) in protection forest. Their vulnerability are affected by: 1) exposure, the climate; 2) sensitivity, covering dependency of coastal community sources of incomes to climate change, location of community sources of incomes close to the source of disaster, and environmental damage; and 3) adaptive capacity, including improved biophysical environment, various sources of incomes, agricultural and fishery technologies, ability to reschedule the activities, changing profession, do nothing, strong community institution, government development program, and intensiveassistance.